Aplikasi teknologi coating untuk peningkatan daya simpan bunga anyelir guna memperluas pasar edible flower - Emmy Darmawati Darmawati; Mila Anisya Rahmi (AGROINTEK, 2023)
Flowers that can be consumed safely are known as edible flowers. Currently, edible flowers are becoming a trend in the floricultural business, besides ornamental flowers. The problem with fresh edible flower agribusiness is that the quality quickly declines, so the market is limited. Transpiration and respiration are one of the causes of fresh flowers being easily damaged. The proper coating will reduce transpiration and respiration and even microbial damage. Carnations are one of the most popular flowers because of their exotic colors. This study aimed to increase the shelf life of carnations as fresh edible flowers with coating technology. The coating materials studied were carrageenan with a concentration of 0.5% and 0.1% and chitosan with a concentration of 0.1% and 0.05%. Quality parameters measured were water content, weight loss, and color. The hedonic test is carried out to determine the limits of consumer acceptance of the quality of edible flowers. The results showed that the best treatment was coating with 0.1% chitosan solution (Q1). This treatment maintained water content, weight loss, and color (L and °hue values) for up to 6 days of storage, with panelists receiving a score of 3 (hedonic 0-5). Increasing the shelf life by three days longer than the control will increase the market reach so that the edible flower agribusiness market can be expanded. The cost of coating with 0.1% chitosan solution applied using the spray method was 95.2 IDR per flower.